Seed fairs: an innovative climate-smart practice to share and obtain stress-tolerant seeds - Odubote, Kolawole; Mulila-Mitti, Joyce; Ajayi, Oluyede C.; Kadzamira, Mariam A.T.J. (Technical Centre for Agricultural and Rural Cooperation, 2019)
A major concern for smallholder farmers at the start of each season is to choose and source seeds, and with the advent of climate change, this is more critical than ever. As part of a CTA-led initiative to help farmers counter drought and other extreme weather events, seed fairs are being organised in Zambia to improve access to quality seed of stress tolerant maize varieties for smallholder farmers.